Between Supplication and Law: A Balaghah-Based Hermeneutic of Qur’anic Du‘a on Family Psychology - Daud Lintang; Sukron Kamil; Achmad Satori Ismail; Siti Amsariah; Anouar Ben Khalifa (Universitas Muhammadiyah Bandung, 2025)
Family life in the Qur’an is not only regulated through legal injunctions but also shaped through supplicatory discourse that forms emotional, ethical, and spiritual orientations. Although Qur’anic duʿāʾ has often been studied as devotional practice, theological expression, or rhetorical beauty, its role in constructing Islamic family psychology remains underexplored. Existing studies on Islamic psychology and family resilience have emphasized religious coping, moral education, and spiritual well-being, yet they rarely examine how the rhetorical structure of Qur’anic family supplications produces psychological and normative meanings. This study aims to analyze how selected Qur’anic duʿāʾ related to spouses, children, parents, descendants, and moral continuity constructs a family psychology situated between supplication and normativity. Using a qualitative textual method, the article applies balāghah-based hermeneutics, thematic Qur’anic analysis, Islamic psychology, religious coping theory, and family resilience theory to selected verses, including QS Maryam [19]:4–6, QS Āl ʿImrān [3]:38, QS Ibrāhīm [14]:40–41, QS al-Baqarah [2]:128–129, QS al-Furqān [25]:74, QS al-Aḥqāf [46]:15, and QS al-Isrāʾ [17]:24. The findings show that Qur’anic duʿāʾ functions as spiritual attachment and emotional regulation, forms intergenerational moral responsibility, constructs family flourishing through qurrata aʿyun, and operates as normative discourse beyond formal family law. The study contributes to Qur’anic studies and Islamic family psychology by proposing duʿāʾ as a hermeneutic site where rhetoric, emotional formation, family ethics, and moral continuity converge.